Suprapatellar nailing of tibial fractures–Indications and technique. Issue 2 (February 2016) - Franke, J.; Hohendorff, B.; Alt, V.; Thormann, U.; Schnettler, R.
Abstract: Intramedullary nailing is the standard procedure for surgical treatment of closed and Gustilo-Anderson Grade I-II° open fractures of the tibial shaft. The use of intramedullary nailing for the treatment of proximal metaphyseal tibia fractures is frequently followed by postoperative malalignment, whereas plate osteosynthesis is associated with higher rates of postoperative infection. Intramedullary nailing of tibial fractures is generally performed through an infrapatellar approach. The injured extremity must be positioned at a minimum of 90° of flexion in the knee joint to achieve optimal exposure of the correct entry point. The tension of the quadriceps tendon causes a typical apex anterior angulation of the proximal fragment. The suprapatellar approach improves reduction of the fracture and reduces the occurrence of malalignment during intramedullary nailing of extra-articular proximal tibial fractures. The knee is positioned in 20° of flexion to neutralise traction forces secondary to the quadriceps muscle, thus preventing an apex anterior angulation of the proximal fragment. An additional advantage of the technique is that it allows the surgeon to avoid or minimise further soft tissue damage because of the distance between the optimal incision point and the usual area of soft tissue damage.